Double-sided processing method for ultrathin infrared square germanium wafer
By adopting double -sided polishing methods and specific process steps in the processing of infrared ultra -thin pheasant films, the problem of low surface flatness difference and processing efficiency in existing technologies has been solved, and high -efficiency and high -quality recipe processing is realized. Meet the market's demand for high -quality products.
Patent Information
- Application Number
- CN202411503680.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-25
AI Technical Summary
The existing infrared ultra-thin germanium square processing methods have problems such as poor surface flatness, low processing efficiency, and serious edge angular corrosion caused by single-side polishing, which cannot meet the market's demand for high-quality products.
Using the double -sided processing method of ultra -thin infrared squares, including the pyrodite square pile sleeve, multi -line cutting, edge backward angle, alkaline liquid corrosion, double -sided polishing and ultrasonic cleaning, through specific polishing formula and Parameter settings to achieve double -sided efficient polishing.
The high-quality surface processing of the square films has been realized. The surface scratches, good parallelism, and smooth edges and corners are smooth and non-etching. The production efficiency has increased by 3-4 times.
Smart Images

Figure HDA0005103223540000011 
Figure HDA0005103223540000012 
Figure HDA0005103223540000021
Abstract
Description
Technical Field
[0001] The invention relates to a double-sided processing method of an ultra-thin infrared germanium square sheet, belonging to the technical field of processing ultra-thin infrared germanium square sheets. Background Art
[0002] As an infrared optical material, germanium has the advantages of high infrared refractive index, wide infrared transmission band, small absorption coefficient, low dispersion, easy processing, flash and corrosion, etc. It is particularly suitable for the materials of windows, lenses, prisms and filters of thermal imagers, infrared radars and other infrared optical devices in military and major civilian applications; high-purity germanium or lithium germanium is used in astronomical gamma spectrometers, nuclear reaction spectrometers and plasma physics X-ray instruments; Si-Ge10 and germanium single crystals doped with mercury, cadmium, copper and gallium are used in infrared detectors, but infrared germanium wafers account for a large proportion of the above-mentioned uses.
[0003] The existing processing methods for infrared ultra-thin germanium square sheets (ultra-thin germanium square sheets: refers to infrared germanium sheets with a thickness of no more than 500 microns, hereinafter referred to as "germanium square sheets") are relatively simple. At present, the research and application level of ultra-precision processing in my country is still backward. For flat parts, most factories can only complete manual grinding and single-sided polishing of a small number of products, and there are still many problems such as poor surface flatness and low processing efficiency. In the field of infrared optics, for the flat ultra-thin germanium square sheets commonly used in infrared optical systems, China can generally only polish one side by one side, and there are also problems such as low processing efficiency, poor surface quality and flatness. However, with the continuous expansion of domestic and international market demand, more and more product orders, and shorter production cycles, the existing classical face-by-face processing method can no longer meet market demand. In addition, some professionals use chemical mechanical rapid polishing methods, but due to the rapid chemical reaction rate, the germanium surface is severely chemically etched, resulting in serious corrosion of the germanium square surface and edge corners, which does not meet customer requirements. To address the above problems, it is imperative to find a processing method that can quickly and efficiently achieve quantitative production and ensure product quality. Summary of the invention
[0004] In view of the above-mentioned technical problems existing in the prior art, the present invention provides a double-sided processing method for ultra-thin infrared square germanium sheets, which fully meets the high-quality surface processing requirements of germanium square sheets, mainly showing: few surface scratches, good parallelism, smooth edge edges and corners without etching, and the production efficiency is increased by 3-4 times.
[0005] In order to solve the above technical problems, the technical solutions adopted by the present invention are as follows:
[0006] A double-sided processing method for ultra-thin infrared square germanium sheets, comprising: square pile sleeve punching of germanium crystal rods, multi-wire cutting, edge chamfering, alkali solution etching, double-sided polishing and ultrasonic cleaning;
[0007] Double-sided polishing includes the following steps:
[0008] 1) Double-sided rough polishing:
[0009] The rough polishing machine uses the 9B double-sided polishing machine produced by Yongtai. The double-sided polishing machine adopts 4-Motor movement mode, that is, the upper fixed plate, lower fixed plate, gear ring and center gear motor can be independently controlled. Without changing the running direction of the gear ring and center gear, the planetary wheel can be easily reversed. The planetary wheel can stably process the workpiece in both forward and reverse rotation, thereby realizing adaptive repair of the fixed plate, and the center gear can also be reversed and repaired separately; the planetary wheel adopts a square planetary wheel;
[0010] The configuration formula of the rough polishing liquid is as follows: high-purity water, nano-alumina or zirconia grinding liquid with a mass concentration of 38-42%, sodium perborate and sodium bicarbonate are uniformly stirred to obtain the rough polishing liquid; in the nano-alumina or zirconia grinding liquid, the particle size of the nano-alumina or zirconia is 80-120 nanometers; the volume ratio of high-purity water to the nano-alumina or zirconia grinding liquid is 30:(6-12); the mass ratio of high-purity water, sodium perborate and sodium bicarbonate is 30:(0.4-0.8):(1-5);
[0011] Processing method: put the corroded wafer into the planetary wheel in turn, the lower plate speed is 30-40 rpm, the upper plate speed is 20-26 rpm, the pressure is 20-60 kg, the ring gear speed is 35-45 rpm, the center gear speed is 15-18 rpm, the polishing liquid (coarse polishing liquid) flow rate is 1500-1800 ml / min, the polishing time is 40-60 minutes, and the polishing cloth uses a polyurethane polishing cloth with 2mm*2mm squares;
[0012] 2) Double-sided polishing;
[0013] The fine polishing machine uses the 9B double-sided polishing machine produced by Chuangji. The double-sided polishing machine adopts 4-Motor motion mode. The upper fixed plate, lower fixed plate, gear ring and sun gear are all independently controlled to achieve the most ideal speed ratio for polishing. The speed ratio of the sun gear relative to the other three speeds can be adjusted steplessly, so that the planetary gear can achieve forward and reverse rotation, meeting the needs of different polishing and repairing processes; the planetary gear adopts a square planetary gear;
[0014] Formula of mixed fine polishing liquid: high-purity water, nano-silicon dioxide grinding liquid with a mass concentration of 20-30%, potassium dichromate and potassium dihydrogen phosphate are stirred evenly to obtain fine polishing liquid; the particle size of nano-silicon dioxide in the nano-silicon dioxide abrasive is 20 nanometers; the volume ratio of high-purity water to nano-silicon dioxide grinding liquid is 30:(8-14); the mass ratio of high-purity water, potassium dichromate and potassium dihydrogen phosphate is 30:(0.3-0.8):(0.3-0.9);
[0015] Processing method: put the rough polished wafers into the planetary wheel in turn, the lower fixed plate speed is 25-35 rpm, the upper fixed plate 18-24 rpm, the pressure is 30-60kg, the ring gear speed is 25-35 rpm, the center gear speed is 10-15 rpm, the polishing liquid (fine polishing liquid) flow rate is 2000-2600ml / min, the polishing time is 20-30 minutes, and the polishing cloth uses a velvet damping cloth with 20mm*20mm squares.
[0016] Due to technical limitations, existing ultra-thin single-crystal germanium wafers can only be processed by single-sided polishing.
[0017] Currently, the limiting speed for double-sided polishing is 60 rpm.
[0018] Due to the special use of infrared ultra-thin germanium square sheets, the quality requirements are also very high. The improper selection of any factor such as polishing type (mechanical polishing and chemical polishing), polishing liquid, polishing parameters, etc. will have a qualitative impact on the quality of infrared ultra-thin germanium square sheets and lead to waste sheets.
[0019] Different crystal materials have different requirements for polishing liquids. This is because the differences in the properties of different crystal materials lead to different effects of the same polishing liquid on different crystal materials, and the differences are even huge. In practical production, it is necessary to develop suitable polishing processes for different crystal materials.
[0020] The present invention realizes double-sided polishing of infrared ultra-thin germanium square sheets by selecting a polishing method between mechanical and chemical mechanical polishing in the polishing step, combining the selection of the formula of the polishing liquid in a specific stage, the selection of the polishing parameters, and the coordinated cooperation of various factors, and the surface quality is good, the parallelism is good, the edges and corners are smooth and there is no etching, and the production efficiency is improved by 3-4 times.
[0021] The sodium perborate is 99% sodium perborate, that is, the purity of the sodium perborate is 99wt%.
[0022] The above-mentioned 4-Motor refers to four motor drives, that is, the upper fixed plate, lower fixed plate, ring gear and center gear motors can all be controlled independently.
[0023] The above-mentioned alkali corrosion includes:
[0024] ① Mix pure water, potassium hydroxide and hydrogen peroxide in a water bath at 40-50° C. to obtain an alkaline solution, wherein the mass ratio of pure water: potassium hydroxide: hydrogen peroxide is (14-16): (2-3): (1-2), and the mass concentration of hydrogen peroxide is 20-25%;
[0025] ② Mix pure water, potassium hydroxide and potassium permanganate in a water bath at 40-50° C. to obtain an alkaline solution, wherein the mass ratio of pure water: potassium hydroxide: potassium permanganate is (14-16): (2-3): (1-1.5);
[0026] ③Put the chamfered sheet into a stainless steel basket, and then put the stainless steel basket into the alkali solution prepared in ① or ②, immerse the wafer in the alkali solution, rotate 58-62° clockwise, and then rotate 116-124° counterclockwise, and repeat this cycle 20-30 times, with a total time of 20-30 seconds. Take out and rinse the wafer with a water gun for 55-60 seconds, and blow dry with a hair dryer.
[0027] The above-mentioned method of uniformly corroding the chamfered germanium square sheet by mixing alkali solution and oxidant can improve the strength of the germanium sheet and the edge smoothness and avoid fragments during processing. The corrosion uses a mixture of alkali solution and oxidant, the alkali mainly uses potassium hydroxide, and the oxidant uses potassium permanganate or hydrogen peroxide.
[0028] Unless otherwise specified, all % in this application are 100% by quality.
[0029] The invention has been found through experiments that the alkaline solution used in step ② has a better effect, which not only increases the corrosion rate, but also significantly improves the parallelism.
[0030] The above-mentioned ultrasonic cleaning includes:
[0031] 1) Add high-purity water, ammonium citrate and chelating agent aminotriacetic acid into an ultrasonic cleaning tank and stir evenly to obtain a cleaning agent; the mass ratio of high-purity water, ammonium citrate and aminotriacetic acid is 50:(2-5):(0.3-0.8);
[0032] 2) Place the polished wafer in a stainless steel basket, then place the stainless steel basket in the cleaning agent, immerse the wafer in the cleaning agent, turn on the ultrasonic wave (40khz) for 60-180 seconds, then place the stainless steel basket in a pure water tank, immerse the wafer in pure water, and turn on the overflow switch to overflow. Overflow cleaning for 120-240 seconds, finally immerse in anhydrous ethanol for 10-15 seconds, take out, and blow dry with a fan.
[0033] The above-mentioned ultrasonic cleaning can remove particles, metal ions and the like.
[0034] The stainless steel flower basket used in each step of the present application is made of stainless steel 04Cr13Ni8Mo2Al.
[0035] The above-mentioned germanium crystal rod square pile sleeve punching rod adopts a vertical ZKG800 series CNC punching machine. The punching rod size length*width is adjustable from 15*15mm to 130*130. The punched rod is flat, smooth, and burr-free, with a roughness of ≤5μm; the sleeve depth is between 30-250mm, and the sleeve is lined with corundum with a particle size of 600-700 mesh.
[0036] To remove the rod, you need to use K9119AB glue to bond the crystal rod to the tooling. After curing, clamp and remove the rod.
[0037] The required square sleeve can be customized according to needs.
[0038] The multi-wire cutting is performed by using a U-600 multi-wire cutting machine; the cutting fluid is a mixture of 3500-4000 mesh corundum and C10, and the viscosity of the cutting fluid is 42-45 mPa·s; the cutting parameters are: line speed 400-500 m / min, worktable rising speed 0.05-0.12 mm / min, cutting line diameter 120 μm, cutting line speed 20-30 m / min, cutting line tension 16-24 N; cutting fluid flow rate 60-80 liters / min; through cutting speed rate control, the parallelism after slicing is ≤10 μm, and there are no scratches, saw marks and other defects on the surface under fluorescent light; the obtained slices are successively cleaned with acetic acid (desizing under acetic acid conditions at 40°C) and anhydrous ethanol, and then blown dry.
[0039] The above-mentioned edge chamfering uses a semi-automatic chamfering machine. The edge chamfer is trapezoidal, the edge chamfer is 5*45°, and the shaft end and shoulder chamfer is 5*45°; the chamfering slope length is adjustable from 1 to 6 mm, the motor speed is ≥3000 rpm, and rounded corners are avoided throughout the entire process.
[0040] The above method uses a chamfering machine to chamfer 8 edges, shaft ends, and 4 shoulders, and the chamfering requirement is controlled within 5*45°. The above method reduces the risk of edge collapse in subsequent processing.
[0041] The invention is safe, reliable and stable and realizes quantitative production.
[0042] The technologies not mentioned in the present invention are all referred to the prior art.
[0043] The double-sided processing method of the ultra-thin infrared square germanium sheet of the present invention adopts a multi-coin cutting square rod, mechanical grinding and chemical mechanical polishing method, and its beneficial effects are mainly reflected in the following aspects:
[0044] 1. This invention improves the parallelism of the square slices. The parallelism of the final product is less than 1.8μm, the saw marks of the slices are small, the roughness is small, and the grinding step is omitted.
[0045] 2. The present invention improves the efficiency of rough polishing and fine polishing, and the processing efficiency can be increased by 3-4 times. The product surface quality has fewer scratches and less dirt, the product first-time qualified rate is high, and the polishing production cost is reduced.
[0046] 3. The present invention effectively improves the surface finish, and the organic acid + chelating agent used in cleaning has a good effect in removing metal ions, thereby improving the cleaning pass rate.
[0047] 4. The present invention solves the problem that chemical mechanical polishing is highly corrosive, resulting in severe corrosion on the surface and edge of the germanium sheet.
[0048] 5. The present invention completely overturns the limitations of traditional infrared technology and opens up new ideas for the processing of ultra-thin germanium square sheets. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 This is a schematic diagram of the structure of an ultra-thin infrared square germanium sheet;
[0050] Figure 2 The surface roughness of the ultra-thin infrared square germanium sheet obtained in Example 1 is measured using a scanning microscope;
[0051] Figure 3 The surface roughness of the ultra-thin infrared germanium square sheet obtained in Example 1 observed under a microscope with 5*10 times magnification, and the microscope has differential interference; DETAILED DESCRIPTION
[0052] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0053] Example 1
[0054] Select germanium cutting crystal rods, doped with antimony, with a resistivity of 1-40Ω·mm, a diameter of 150±2mm, and a rod size of length*width*thickness: 26.5*26.5*200mm. Two germanium square rods are selected, and the thickness of the finished product is 26.5mm*26.5mm*500μm. Follow the processing steps below:
[0055] 1. Square pile rod digging rod
[0056] ①. Install a 30.5*30.5*210mm (wall thickness 2mm) square sleeve on the ZKG800 series CNC rod-pulling machine, and line the sleeve with 600-mesh corundum.
[0057] ②. Glue the rod-pulling glue (A+B resin glue 1:1 mixture, model: K9119AB) on the tooling and cool for 4 hours, then transfer it to the equipment for support, and start the rod-pulling machine. The rod-pulling size is 26.5*26.5*200mm.
[0058] ③. The surface of the rod is flat, smooth, and burr-free, with a roughness of ≤5μm.
[0059] 2. Multi-wire cutting
[0060] ①. U600 multi-wire sawing machine is used for slicing. The cutting parameters are as follows: reciprocating speed 450m / min, table rising speed 1mm / min, cutting wire diameter 120μm, cutting new wire speed 25m / min, cutting wire tension 20N; the cutting fluid is a mixture of 4000 mesh corundum and C10, the cutting fluid viscosity is 45mPa·s, and the cutting fluid flow rate is 65L / min; cutting thickness: 620±10μm, parallelism after slicing ≤10μm;
[0061] ②. There are no scratches, saw marks or other defects on the surface under fluorescent light.
[0062] ③. Degumming the cut pieces in acetic acid at 40°C, then cleaning and dehydrating with anhydrous ethanol, and drying with a hair dryer.
[0063] 3. Chamfer
[0064] ①. Use a semi-automatic chamfering machine, model: hc0001 double-station; the edge chamfer is trapezoidal, and the edge chamfer is required to be 5*45°;
[0065] ②, shaft end and shaft shoulder chamfer 5*45°; chamfer slope length 4mm, motor speed 3500 rpm;
[0066] ③. Chamfer 8 edges, shaft ends, and 4 shoulders. The chamfering requirement is controlled within 5*45°. The chamfering method controls the edge angle and its edge shape.
[0067] 4. Corrosion
[0068] ①. Use a measuring cup to measure 15L pure water, add 2500g potassium hydroxide and 1.5L hydrogen peroxide, pour them into the glass fiber reinforced plastic and stir evenly, heat in a water bath to 40-50℃, stir with a glass rod to dissolve and mix to obtain lye;
[0069] ②. Place the chamfered germanium wafer into a stainless steel basket (made of special stainless steel 04Cr13Ni8Mo2Al), and then place the stainless steel basket into the prepared alkali solution. Immerse the wafer in the alkali solution, quickly rotate 60° clockwise, then 120° counterclockwise, and repeat the cycle 30 times for a total of 30 seconds. Take out and rinse the wafer with a water gun for 60 seconds, and blow dry it with a hair dryer.
[0070] 5. Polishing
[0071] ① Rough polishing:
[0072] The rough polishing machine uses the 9B double-sided polishing machine produced by Yongtai. The double-sided polishing machine adopts 4-Motor movement mode, that is, the upper fixed plate, lower fixed plate, gear ring, and center gear motor can be independently controlled. Without changing the running direction of the gear ring and the center gear, the planetary wheel can be easily reversed. The planetary wheel can stably process the workpiece in both forward and reverse rotation, thereby realizing adaptive repair of the fixed plate, and the center gear can also be reversed and repaired separately; the planetary wheel adopts a square planetary wheel;
[0073] Formula for mixed rough polishing liquid: add 30L of high-purity water to the preparation barrel, add 10L of nano-zirconia grinding liquid (mass concentration is 40%, nano-zirconia particle size is 100nm), then add 500g of 99% sodium perborate, and then add 300g of sodium bicarbonate, stir evenly and use.
[0074] Processing method: put the germanium sheets obtained by corrosion into the planetary wheel in turn, processing procedure: lower fixed plate speed 35 rpm, upper fixed plate 24 rpm, pressure 40kg, ring gear speed 38 rpm, center gear speed 16 rpm, polishing liquid flow 1600ml / min, polishing time 50 minutes, polishing cloth used is CP-J-32 produced by Sichuan Research Technology.
[0075] ②, Fine polishing
[0076] The fine polishing machine uses the 9B double-sided polishing machine produced by Chuangji. The double-sided polishing machine is driven by four motors (4-Motor). The upper fixed plate, lower fixed grinding plate, gear ring and sun gear can be adjusted individually to achieve the most ideal speed ratio for polishing. The speed ratio of the sun gear relative to the other three speeds can be adjusted steplessly, so that the cruise wheel can achieve forward and reverse rotation, meeting the needs of different polishing and repairing processes; the planetary wheel adopts a square planetary wheel;
[0077] Formula for mixed polishing liquid: add 30L high-purity water to the medicine barrel, add 10L nano-silicon dioxide grinding liquid (mass concentration is 25%, nano-silicon dioxide particle size is 20 nanometers), then add 500g of oxidant potassium dichromate, add 500g of buffer potassium dihydrogen phosphate, stir evenly and use;
[0078] The germanium sheets obtained by rough polishing are placed into the planetary wheel in sequence. The processing procedure is: lower fixed plate speed 30 rpm, upper fixed plate 20 rpm, pressure 30kg, ring gear speed 28 rpm, center gear speed 12 rpm, polishing liquid flow 2400ml / min, polishing time 25 minutes, and the polishing cloth used is JP-J-32 produced by Jizhi Technology.
[0079] 6. Cleaning
[0080] ①. Add 50L of high-purity water into the ultrasonic cleaning tank, weigh 3kg of ammonium citrate on a balance and put it into the cleaning tank for stirring, then add 500g of chelating agent aminotriacetic acid and stir evenly to obtain the cleaning agent;
[0081] ②. Put the germanium wafers obtained by fine polishing into a stainless steel basket, put them in a storage box, immerse the wafers in water in the storage box, and send them to the cleaning process. Put the stainless steel basket into the ultrasonic cleaning tank, immerse the wafers in the cleaning agent, turn on the ultrasonic wave (40khz) for 120 seconds, then put the stainless steel basket into the pure water tank, immerse the wafers in pure water, and turn on the overflow switch to overflow, and overflow cleaning for 160 seconds. Put it into anhydrous ethanol and immerse it for 12 seconds, take it out, and blow it dry with a fan. Product thickness: 500±5μm. There is no damage or mechanical damage in the whole process, and the product qualification rate reaches 100%. Compared with the existing single-sided polishing, the production efficiency is increased by 3-4 times.
[0082] 7. Testing
[0083] ①. The product is tested for parallelism using a testing instrument. The number of samples tested is 120, and the parallelism is ≤1.8μm
[0084] ② Check the surface quality with a strong light to ensure there are no scratches, fog spots, particulate matter, white fog and other defects;
[0085] ③. Microscope inspection shows that the edges, sides, shaft ends and shoulders are of high precision, with a precision deviation of ≤±0.02mm and no defects such as chemical corrosion.
[0086] ④. After cleaning, the surface is clean, translucent, uniform and delicate, with a roughness of ≤0.08nm.
[0087] Example 2
[0088] Different from Example 1, the corrosion step 4 is:
[0089] ①. Use a measuring cup to measure 15L pure water, add 2500g potassium hydroxide and 1200g potassium permanganate, pour them into the glass fiber reinforced plastic and stir evenly, heat in a water bath to 40-50℃, stir with a glass rod to dissolve and mix to obtain lye;
[0090] ②. Place the chamfered germanium wafer into a stainless steel basket (made of special stainless steel 04Cr13Ni8Mo2Al), and then place the stainless steel basket into the prepared alkali solution. Immerse the wafer in the alkali solution, quickly rotate 60° clockwise, then 120° counterclockwise, and repeat the cycle 20 times for a total of 20 seconds. Take out and rinse the wafer with a water gun for 60 seconds, and blow dry it with a hair dryer.
[0091] The remaining steps are consistent with Example 1. Compared with Example 1, the corrosion efficiency is increased by 33.3% and the parallelism is improved by 5.6%.
[0092] Example 3
[0093] Select a germanium cutting crystal rod, doped with antimony, with a resistivity of 1-40Ω·mm, a diameter of 150±2mm, and a rod size of 76.5*76.5*200mm in length*width*thickness. The finished product is 76.5mm*76.5mm*500μm. Follow the following processing steps:
[0094] 1. Square pile rod digging rod
[0095] ①. Install a 82.5*82.5*210mm square sleeve (wall thickness 2mm) on the ZKG800 series CNC rod-pulling machine, and line the sleeve with 700-mesh corundum.
[0096] ②. Glue the rod-cutting glue (A+B resin glue 1:1 mixture, model: K9119AB) on the tooling and cool for 4 hours, then transfer to the equipment for support, start the rod-cutting machine, and the rod-cutting size is 76.5*76.5*200mm. The remaining crystal rods can be cut into small sizes again.
[0097] ③. The surface of the rod is flat, smooth, and burr-free, with a roughness of ≤5μm.
[0098] 2. Multi-wire cutting
[0099] ①. U600 multi-wire sawing machine is used for slicing. Cutting parameters: reciprocating line speed 400m / min, worktable rising speed 0.9mm / min, cutting line diameter 120μm, cutting new line speed 24m / s, cutting line tension 20N; cutting fluid is a mixture of 3500 mesh corundum and C10, cutting fluid viscosity 42mPa·s, cutting fluid flow 70L / min; cutting thickness: 620±10μm, parallelism after slicing ≤10μm;
[0100] ②. There are no scratches, saw marks or other defects on the surface under fluorescent light.
[0101] ③. Degumming the cut pieces in acetic acid at 40°C, then cleaning and dehydrating with anhydrous ethanol, and drying with a hair dryer.
[0102] 3. Chamfer
[0103] ①. Use hc0001 double station, the edge chamfer is trapezoidal, and the edge chamfer is required to be 5*45°;
[0104] ②, shaft end and shaft shoulder chamfer 5*45°; chamfer slope length 4.8mm, motor speed 3500 rpm;
[0105] ③. Chamfer 8 edges, shaft ends, and 4 shoulders. The chamfering requirement is controlled at 4.9*44°59′. The chamfering method controls the edge angle and its edge shape.
[0106] 4. Corrosion
[0107] ①. Use a measuring cup to measure 30L of pure water, add 5200g of potassium hydroxide and 3.0L of hydrogen peroxide, pour them into the glass fiber reinforced plastic and stir evenly, heat in a water bath to 40-50℃, stir with a glass rod to dissolve and mix to obtain lye;
[0108] ②. Place the chamfered germanium wafer into a stainless steel basket (made of special stainless steel 04Cr13Ni8Mo2Al), and then place the stainless steel basket into the prepared alkali solution. Immerse the wafer in the alkali solution, quickly rotate 60° clockwise, then 120° counterclockwise, and repeat the cycle 30 times for a total of 30 seconds. Take out and rinse the wafer with a water gun for 60 seconds, and blow dry it with a hair dryer.
[0109] 5. Polishing
[0110] ① Rough polishing:
[0111] The rough polishing machine uses the 9B double-sided polishing machine produced by Yongtai. The double-sided polishing machine adopts 4-Motor (3-Motor is optional), that is, the upper fixed plate, lower fixed plate, gear ring, and center gear motor can be independently controlled. Without changing the running direction of the gear ring and center gear, the planetary wheel can be easily reversed. The planetary wheel can stably process the workpiece in both forward and reverse rotations, thereby realizing adaptive repair of the fixed plate, and the center gear can also be reversed and repaired separately; the planetary wheel adopts a square planetary wheel;
[0112] Formula for mixed rough polishing liquid: add 30L of high-purity water to the preparation barrel, add 10L of nano-zirconia grinding liquid (mass concentration is 40%, nano-zirconia particle size is 100nm), then add 600g of oxidant sodium perborate, and then add 300g of buffer sodium bicarbonate, stir evenly and use.
[0113] Processing method: put the germanium sheets obtained by corrosion into the planetary wheel in turn, processing procedure: lower fixed plate speed 35 rpm, upper fixed plate 24 rpm, pressure 40kg, ring gear speed 40min, center gear speed 18 rpm, polishing liquid flow 1600ml / min, polishing time 50 minutes, polishing cloth used is CP-J-32 produced by Sichuan Research Technology.
[0114] ②, Fine polishing
[0115] The fine polishing machine uses the 9B double-sided polishing machine produced by Chuangji. The double-sided polishing machine is driven by four motors, which can adjust the speed of the upper fixed plate, lower fixed grinding plate, gear ring and sun gear separately, so that the polishing can reach the most ideal speed ratio. The speed ratio of the sun gear relative to the other three speeds can be adjusted steplessly, so that the cruise wheel can realize forward and reverse rotation, meeting the needs of different polishing and repairing processes; the planetary wheel adopts a square planetary wheel;
[0116] Formula for mixed polishing liquid: add 30L high-purity water to the medicine barrel, add 10L nano-silicon dioxide grinding liquid (mass concentration is 25%, nano-silicon dioxide particle size is 20 nanometers), then add 500g of oxidant potassium dichromate, add 500g of buffer potassium dihydrogen phosphate, stir evenly and use;
[0117] The germanium sheets obtained by rough polishing are placed into the planetary wheel in sequence. The processing procedure is: lower fixed plate speed 28 rpm, upper fixed plate 24 rpm, pressure 35kg, ring gear speed 30 rpm, center gear speed 14 rpm, polishing liquid flow 2600ml / min, polishing time 20 minutes, and the polishing cloth used is JP-J-32 produced by Jizhi Technology.
[0118] 6. Cleaning
[0119] ①. Add 50L of high-purity water to the ultrasonic cleaning tank, weigh 3.5kg of ammonium citrate on a balance and put it into the cleaning tank for stirring, then add 600g of chelating agent aminotriacetic acid and stir evenly to obtain the cleaning agent;
[0120] ②. Put the germanium wafers obtained by fine polishing into a stainless steel basket, put them in a storage box, immerse the wafers in water in the storage box, and send them to the cleaning process. Put the stainless steel basket into the ultrasonic cleaning tank, immerse the wafers in the cleaning agent, turn on the ultrasonic wave (40khz) for 120 seconds, then put the stainless steel basket into the pure water tank, immerse the wafers in pure water, and turn on the overflow switch to overflow, and overflow cleaning for 160 seconds. Put it into anhydrous ethanol and immerse it for 12 seconds, take it out, and blow it dry with a fan. Product thickness: 500±5μm. There is no damage or mechanical damage in the whole process, and the product qualification rate reaches 100%.
[0121] 7. Testing
[0122] ①. The product is tested for parallelism using a testing instrument. The number of samples tested is 120, and the parallelism is ≤1.8μm
[0123] ② Check the surface quality with a strong light to ensure there are no scratches, fog spots, particulate matter, white fog and other defects;
[0124] ③. Microscope inspection shows that the edges, sides, shaft ends and shoulders are of high precision, with a precision deviation of ≤±0.02mm, and there are no defects such as chemical corrosion.
[0125] ④. After cleaning, the surface is clean, translucent, uniform and delicate, with a roughness less than 0.08nm.
[0126] Comparative Example 1
[0127] The difference from Example 1 is that in the multi-wire cutting of step 2, the new cutting line speeds of 15m / min and 35m / min are used respectively, and the rest are referred to Example 1. The results show that at the cutting speeds of 15m / min and 35m / min, saw marks of varying degrees are left on the cutting disc. The reason may be that the cutting speed does not match other parameters, resulting in the cutting line transition staying or being too fast, which will leave pull marks on the cutting disc. After testing, the parallelism deviation is ≤3.9μm and the roughness is ≤0.5nm.
[0128] Comparative Example 2
[0129] The difference from Example 1 is that in step 5, the nano-zirconia grinding liquid in the rough polishing and the nano-silicon dioxide grinding liquid in the fine polishing are interchanged. The rest are all referred to Example 1. The results show that the parallelism deviation is ≤6.9μm and the roughness is ≤2nm. The reason may be that on the one hand, the silicon grinding liquid for rough polishing and fine polishing does not match the other parameters, and on the other hand, the use of silicon dioxide grinding liquid in rough polishing has limited contribution to the polishing effect, while the use of nano-zirconia grinding liquid in fine polishing is not conducive to the improvement of roughness and parallelism.
[0130] Comparative Example 3
[0131] The difference from Example 1 is that in step 5, the nano-zirconia grinding liquid in the rough polishing and the nano-silicon dioxide grinding liquid in the fine polishing are omitted. The rest are all referred to Example 1. The results show that the parallelism deviation is ≤7.5μm and the roughness is ≤3.5nm. That is, the addition of the nano-zirconia grinding liquid in the rough polishing and the nano-silicon dioxide grinding liquid in the fine polishing has a significant effect on improving the product quality.
[0132] Comparative Example 4
[0133] The difference from Example 1 is that in step 5, 99% of the sodium perborate in the rough polishing is replaced by ammonium persulfate, potassium hypochlorite, potassium perchlorate or potassium peroxide. The rest is referred to Example 1. The results show that the parallelism deviation is ≤5.2μm and the roughness is ≤1.6nm. Compared with Example 1, the surface quality is significantly reduced, indicating that the selection of the oxidant in the rough polishing is very critical.
[0134] Comparative Example 5
[0135] The difference from Example 1 is that in step 5, potassium dichromate in the fine polishing is replaced by ammonium persulfate, potassium hypochlorite, potassium perchlorate or potassium peroxide. The rest is referred to Example 1. The results show that the parallelism deviation is ≤5.8μm and the roughness is ≤1.9nm. Compared with Example 1, the surface quality is significantly reduced, indicating that the selection of oxidant in fine polishing is also very critical.
[0136] Comparative Example 6
[0137] The difference from Example 1 is that in step 5, during the rough polishing, the lower platen speed is 45 rpm, the upper platen speed is 28 rpm, the ring gear speed is 50 rpm, and the center gear speed is 20 rpm. The rest is the same as Example 1. The results show that the thickness does not meet the use requirements and is unqualified.
[0138] Comparative Example 7
[0139] The difference from Example 1 is that in step 5, during the rough polishing, the lower platen speed is 25 rpm, the upper platen speed is 18 rpm, the ring gear speed is 30 rpm, and the center gear speed is 12 rpm. The rest are all referenced to Example 1. The results show that the parallelism deviation is ≤3.8μm and the roughness is ≤1.3nm. The parameters do not match.
[0140] Comparative Example 8
[0141] The difference from Example 1 is that in step 5, during fine polishing, the lower platen speed is 40 rpm, the upper platen speed is 30 rpm, the ring gear speed is 20 rpm, and the center gear speed is 8 rpm. The rest are all referenced to Example 1. The results show that the parallelism deviation is ≤2.9μm and the roughness is ≤1.2nm. The parameters do not match.
[0142] Comparative Example 9
[0143] The difference from Example 1 is that no aminotriacetic acid is added in the cleaning of step 6. The rest is the same as Example 1. The results show that there are obvious fog spots and particulate matter on the surface of the germanium wafer, and the qualified rate is 65%.
Claims
1. A method for double-sided processing of ultra-thin infrared square germanium sheets, characterized in that: include: Germanium crystal rod square pile sleeve punching, multi-wire cutting, edge chamfering, alkali corrosion, double-sided polishing and ultrasonic cleaning; Double-sided polishing includes the following steps: 1) Double-sided rough polishing: The rough polishing machine uses a 9B double-sided polishing machine, which adopts a 4-Motor motion mode. The upper fixed plate, lower fixed plate, gear ring and center gear motors are all independently controlled. Without changing the running direction of the gear ring and center gear, the planetary wheel can be rotated forward and reversely. The planetary wheel adopts a square planetary wheel. Preparation of rough polishing liquid: Mix high-purity water, nano-alumina or zirconium oxide grinding liquid with a mass concentration of 38-42%, sodium perborate and sodium bicarbonate, and stir evenly to obtain rough polishing liquid; In the nano-alumina or zirconia grinding liquid, the particle size of the nano-alumina or zirconia is 80-120 nanometers; the volume ratio of high-purity water to the nano-alumina or zirconia grinding liquid is 30:(6-12); the mass ratio of high-purity water, sodium perborate and sodium bicarbonate is 30:(0.4-0.8):(1-5); Processing method: put the corroded wafer into the planetary wheel in turn, the lower plate speed is 30-40 rpm, the upper plate speed is 20-26 rpm, the pressure is 20-60 kg, the ring gear speed is 35-45 rpm, the center gear speed is 15-18 rpm, the polishing liquid flow rate is 1500-1800 ml / min, the polishing time is 40-60 minutes, and the polishing cloth is a polyurethane polishing cloth with 2mm*2mm squares; 2) Double-sided polishing; The fine polishing machine uses a 9B double-sided polishing machine, which adopts a 4-Motor motion mode. The upper fixed plate, lower fixed plate, gear ring and sun gear are all independently controlled. The speed ratio of the sun gear relative to the other three speeds can be steplessly adjusted to enable the planetary gear to achieve forward and reverse rotation; the planetary gear adopts a square planetary gear; Formula of mixed fine polishing liquid: high-purity water, nano-silicon dioxide grinding liquid with a mass concentration of 20-30%, potassium dichromate and potassium dihydrogen phosphate are stirred evenly to obtain fine polishing liquid; the particle size of nano-silicon dioxide in the nano-silicon dioxide abrasive is 20 nanometers; the volume ratio of high-purity water to nano-silicon dioxide grinding liquid is 30:(8-14); the mass ratio of high-purity water, potassium dichromate and potassium dihydrogen phosphate is 30:(0.3-0.8):(0.3-0.9); Processing method: put the rough-polished wafers into the planetary wheel in turn, the lower fixed plate speed is 25-35 rpm, the upper fixed plate speed is 18-24 rpm, the pressure is 30-60kg, the ring gear speed is 25-35 rpm, the center gear speed is 10-15 rpm, the polishing liquid flow rate is 2000-2600ml / min, the polishing time is 20-30 minutes, and the polishing cloth uses a velvet damping cloth with 20mm*20mm squares.
2. The method for double-sided processing of ultra-thin infrared germanium square sheets according to claim 1, characterized in that: Alkaline corrosion includes: ① Mix pure water, potassium hydroxide and hydrogen peroxide in a water bath at 40-50° C. to obtain an alkaline solution, wherein the mass ratio of pure water: potassium hydroxide: hydrogen peroxide is (14-16): (2-3): (1-2), and the mass concentration of hydrogen peroxide is 20-25%; ② Mix pure water, potassium hydroxide and potassium permanganate in a water bath at 40-50° C. to obtain an alkaline solution, wherein the mass ratio of pure water: potassium hydroxide: potassium permanganate is (14-16): (2-3): (1-1.5); ③Put the chamfered sheet into a stainless steel basket, and then put the stainless steel basket into the alkali solution prepared in ① or ②, immerse the wafer in the alkali solution, rotate 58-62° clockwise, and then rotate 116-124° counterclockwise, and repeat this cycle 20-30 times, with a total time of 20-30 seconds. Take out and rinse the wafer with a water gun for 55-60 seconds, and blow dry with a hair dryer.
3. The double-sided processing method of the ultra-thin infrared germanium square sheet according to claim 2, characterized in that: Step ③, place the stainless steel flower basket into the alkaline solution prepared in step ②.
4. The double-sided processing method of the ultra-thin infrared germanium square sheet according to any one of claims 1 to 3, characterized in that: Ultrasonic cleaning includes: 1) Add high-purity water, ammonium citrate and chelating agent aminotriacetic acid into an ultrasonic cleaning tank and stir evenly to obtain a cleaning agent; the mass ratio of high-purity water, ammonium citrate and aminotriacetic acid is 50:(2-5):(0.3-0.8); 2) Place the polished wafer in a stainless steel basket, then place the stainless steel basket in the cleaning agent, immerse the wafer in the cleaning agent, turn on the ultrasonic wave for 60-180 seconds, then place the stainless steel basket in a pure water tank, immerse the wafer in pure water, and turn on the overflow switch to overflow. Overflow cleaning for 120-240 seconds, finally immerse in anhydrous ethanol for 10-15 seconds, take out, and blow dry with a fan.
5. The double-sided processing method of the ultra-thin infrared germanium square sheet according to any one of claims 1 to 3, characterized in that: The stainless steel flower baskets used in each step are made of stainless steel 04Cr13Ni8Mo2Al.
6. The method for double-sided processing of an ultra-thin infrared germanium square sheet according to any one of claims 1 to 3, characterized in that: The square pile sleeve of germanium crystal rod is hollowed out by vertical ZKG800 series CNC hollowing machine. The hollowing size is adjustable from 15*15mm to 130*130 in length and width. The hollowed rod is flat, smooth, and burr-free, with a roughness of ≤5μm. The sleeve depth is between 30-250mm, and the sleeve is lined with corundum with a particle size of 600-700 mesh.
7. The double-sided processing method of the ultra-thin infrared germanium square sheet according to any one of claims 1 to 3, characterized in that: Multi-wire cutting, using U-600 multi-wire cutting machine for slicing; the cutting fluid used is a mixture of 3500-4000 mesh corundum and C10, and the viscosity of the cutting fluid is 42-45mPa·s; cutting parameters: reciprocating linear speed 400-500m / min, worktable rising speed 0.05-0.12mm / min, cutting wire diameter 120μm, cutting new wire linear speed 20-30m / min, cutting wire tension 16-24N; cutting fluid flow 60-80L / min; the obtained slices are cleaned with acetic acid and anhydrous ethanol in turn, and then blown dry.
8. The method for double-sided processing of an ultra-thin infrared germanium square sheet according to any one of claims 1 to 3, characterized in that: Edge chamfering, use semi-automatic chamfering machine, model: hc0001 double-station, edge chamfering is trapezoidal, edge chamfering is 5*45°, shaft end and shoulder chamfering is 5*45°; chamfering slope length is adjustable from 1-6mm, motor speed ≥3000 rpm.
Citation Information
Patent Citations
Ultrathin single crystal germanium wafer processing method
CN103862354A
Polishing solution for chemically mechanically polishing germanium crystal and application method
CN104449404A
Method for polishing two sides of germanium wafer
CN114800222A
Cleaning method of ultrathin germanium single crystal polished wafer
CN114999897A
Germanium wafer double-polishing process and device and germanium wafer
CN115070512A